Luke the Chronicler : The Narrative Arc of Samuel-Kings and Chronicles in Luke-Acts - Giacobbe, Mark S. (Biblical Interpretation Series, 2023)
This book proposes a fresh understanding of the literary composition of Luke-Acts. Picking up on the ancient practice of literary mimesis , the author argues that Luke's two-part narrative is subtly but significantly modeled on the two-part narrative found in the books of Samuel-Kings and Chronicles. Specifically, Luke's gospel presents Jesus as the promised, ultimate Davidide, while the Book of Acts presents the disciples of Jesus as the heirs of the kingdom of David. In addition to the proposal concerning the composition of Luke-Acts, the book offers compelling insights on the genre of Luke-Acts and the purpose of Acts. .